Strategia doskonalenia systemów informacyjnych w organizacjach zorientowanych na zarządzanie wiedzą - Wydmuch, Gracja (Strategy of Information Systems' Improvement in Knowledge Management Oriented Organizations, 2007)
The article presents knowledge resources as the low structuralized category placement source in information system improving. Presented cases point to the differences between the strategies in various types of organizations. The difficulties in the organization knowledge formalization are shown. We can conclude that in the field of knowledge resources even the effective computer systems cannot work properly without human/social factor. Knowledge is the context depiction of information that forces the action of continuous improving of existing information systems towards intellectual potential support in organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 197-206